2013
DOI: 10.1371/journal.pone.0062318
|View full text |Cite
|
Sign up to set email alerts
|

High Human Bocavirus Viral Load Is Associated with Disease Severity in Children under Five Years of Age

Abstract: Human bocavirus (HBoV) is a parvovirus and detected worldwide in lower respiratory tract infections (LRTIs), but its pathogenic role in respiratory illness is still debatable due to high incidence of co-infection with other respiratory viruses. To determine the prevalence of HBoV infection in patients with LRTI in Shanghai and its correlation with disease severity, we performed a 3-year prospective study of HBoV in healthy controls, outpatients and inpatients under five years of age with X-ray diagnosed LRTIs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
53
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 25 publications
11
53
1
6
Order By: Relevance
“…По данным отечественных исследователей, у больных hBoV-инфекцией установлено превалирование клини-ческой формы с изолированными воспалительными поражениями ВДП (назофарингит) -75,2%, реже отме-чался острый и обструктивный бронхит (16,2 и 8,5%), заболевание бокавирусной инфекцией чаще протекало в среднетяжелой форме (84,6%) с острым началом забо-левания [18,[26][27][28].…”
Section: бронхопульмонология лорunclassified
See 1 more Smart Citation
“…По данным отечественных исследователей, у больных hBoV-инфекцией установлено превалирование клини-ческой формы с изолированными воспалительными поражениями ВДП (назофарингит) -75,2%, реже отме-чался острый и обструктивный бронхит (16,2 и 8,5%), заболевание бокавирусной инфекцией чаще протекало в среднетяжелой форме (84,6%) с острым началом забо-левания [18,[26][27][28].…”
Section: бронхопульмонология лорunclassified
“…В 2005 г. в Швеции Т. Алландером с соавт. был описан новый респира-торный вирус, принадлежащий к семейству Parvoviridae, получивший название «бокавирус человека» (human Bocavirus, hBoV), который был выделен от младенцев и детей, страдающих острыми респираторными заболевани-ями верхних и нижних дыхательных путей [4,26]. Позднее hBoV был обнаружен у 1,5-19% больных ОРЗ в Австралии, Японии, Канаде, Соединенных Штатах, Франции, Германии, Корее, Таиланде, Великобритании, Южной Африке, Китае, Швейцарии, Финляндии, Италии, Бразилии, Иордании, Нидерландах и Иране, а также у 1% здоровых лиц [5].…”
unclassified
“…However, papers on this subject show contradictory results. There are some reports suggest that there is no relation between multiple viral ARI and disease severity [68][69][70][71] , while others indicate a higher disease severity in children with a mixed respiratory infection 72,73 .…”
Section: Multiple-viral Infectionsmentioning
confidence: 99%
“…Sommige onderzoekers suggereren een positieve relatie hiertussen [63][64][65][66][67][68][69][70][71][72] , terwijl anderen die relatie niet zien [73][74][75][76][77][78] In de kindergeneeskunde praktijk is virale diagnostiek vaak gebruikt als een enkelvoudige meting bij eerste presentatie van een kind op de spoedeisende hulpafdeling of polikliniek. Deze omstandigheden zijn echter niet optimaal om de relatie tussen viral load en ziekte-ernst te bestuderen, omdat viral load een dynamisch proces is.…”
Section: Viral Loadunclassified
“…Retrospective studies based on detection of HBoV1 infection and its correlation with signs and symptoms registered at the events of positive samples showed that the primary infection causes illness in children [19,20]. Additionally, symptoms have been shown to depend on high viral loads [10,[21][22][23][24]. However, HBoV1 natural history of infection and the genuine clinical manifestations associated remain challenging, especially in the scenario of a persistent infection.…”
Section: Introductionmentioning
confidence: 99%